KADAR ASAM URAT DAN PROTEIN PLASMA DARAH AYAM KAMPUNG: PENGARUH TARAF PROTEIN RANSUM DAN LAMA PEMELIHARAAN: URIC ACID AND PROTEIN PLASMA LEVEL IN NATIVE CHICKEN: BASED ON DIETARY PROTEIN LEVEL IN STAGES OF AGE - Fatmarischa, Novemia; Rizkuna, Akhmat; Ardhani, Fikri (Tropical Animal Science, 2025)
The study aim to analyze the effect of dietary protein level in stages of age on protein usage measured by the level of uric acid and protein plasma in native chicken blood. Material used were 168 chicks (unsex) with average body weight 28,68 ± 1,13 g/chick. The treatments are dietary protein levels 22% for 3 weeks, continued with 15% for 7 weeks (T0), dietary protein levels 18% for 4 weeks, continued with 16% for 6 weeks (T1), dietary protein levels 18% for 2 weeks, continued with 16% for 4 weeks and 14% for 4 weeks (T2), dietary protein levels 18% for 3 weeks, continued with 16% for 3 weeks and 14% for 4 weeks (T3). This research used completely randomized design with 4 treatments and 6 replicates. Each experimental unit consisted of 6 chickens. The average of T0, T1, T2, dan T3 simultaneously for feed efficiency were 36.61; 28.84; 25.39; 21.72. The average of uric acid on blood is 4,92 mg/dl; 4,92 mg/dl; 5,08 mg/dl; and 5,25 mg/dl and protein plasma 2,23 g/dl; 1,84 g/dl; 2,33 g/dl; dan 1,79 g/dl. In conclusion, the protein level in raising period had significant effect on feed efficiency but do not effect on uric acid and protein plasma in 10-week-old native chicken.